ESTABLISHING A TERRESTRIAL CHRONOLOGICAL FRAMEWORK AS A BASIS FOR BIOSTRATIGRAPHICAL COMPARISONS - Tzedakis P.C.; Andrieu V.; de Beaulieu J.L.; Birks H.J.B.; Crowhurst S.; Follieri M.; Hooghiemstra H.; Magri D.; Reille M.; Sadori L.; Shackleton N.J.; Wijmstra T.A. (My University, 2001)
The palynological signature of interglacial deposits in the fragmentary European terrestrial record has often been used as the basis for determining their chronostratigraphical position and ultimately their age. This has placed emphasis on the presence/absence and abundance of certain characteristic taxa, but given the lack of continuous stratigraphies and independent chronologies, it has been difficult to assess the extent to which this strategy has produced reliable schemes. Here, an alternative approach is adopted whereby a chronological framework is developed for long and continuous pollen sequences from southern Europe. This in turn allows the emergence of a complete stratigraphical scheme of major vegetation events for the last 430 thousand years (ka) and the evaluation of the stage record of different taxa and their potential diagnostic value for biostratigraphical correlation. The comparison shows distinct similarities among some temperate stages of the terrestrial equivalent complexes of Marine Isotope Stages (MIS) 5 and 7 and also of MIS 9 and 11, but examination of combined records of taxa provides a possibility to differentiate between individual stages. A numerically-derived dichotomous key for the terrestrial stages based on the palynological records of 10 taxa is presented. Carpinus, Fagus, Abies, Pterocarya and Buxus emerge as the best 'indicator pollen types' because of their variable behaviour from one stage to the next, possibly a result of their late expansion within a temperate stage or reduced genetic variability. The analysis shows that the palynological signature of a temperate deposit can constrain the range of chronostratigraphical possibilities, but vegetation and palynological variability arising from local factors could result in difficulties in making a definite assignment at individual sites.